2017
DOI: 10.1016/j.socscimed.2017.03.061
|View full text |Cite
|
Sign up to set email alerts
|

Problematic social media use and depressive symptoms among U.S. young adults: A nationally-representative study

Abstract: Rationale Depression is the leading cause of disability worldwide. The suggested association between social media use (SMU) and depression may be explained by the emerging maladaptive use pattern known as problematic social media use (PSMU), characterized by addictive components. Objective We aimed to assess the association between PSMU and depressive symptoms—controlling for overall time and frequency of SMU—among a large sample of U.S. young adults. Methods In October 2014, participants aged 19–32 (N = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
241
2
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(302 citation statements)
references
References 53 publications
17
241
2
10
Order By: Relevance
“…The strongest direct predictor of PSMU was depression and it was more strongly related to PSMU among high school students. This result is in line with the study of Shensa et al (2017) which indicated that PSMU is strongly associated with increased depressive symptoms. Adolescence is a psychologically more fragile period for individuals in which depression is more commonly seen among students (Riglin et al 2016) and is more positively associated with antisocial behaviors (Choi et al 2016).…”
Section: Discussionsupporting
confidence: 92%
“…The strongest direct predictor of PSMU was depression and it was more strongly related to PSMU among high school students. This result is in line with the study of Shensa et al (2017) which indicated that PSMU is strongly associated with increased depressive symptoms. Adolescence is a psychologically more fragile period for individuals in which depression is more commonly seen among students (Riglin et al 2016) and is more positively associated with antisocial behaviors (Choi et al 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Studies such as Appel, Gerlach, & Crusius (2015), Tandoc, Ferrucci & Duffy (2015), Verduyn et al (2015), Taylor & Strutton (2016), Christakis & Shakya (2017), and Shensa et al (2017) document recent evidence on connections between social-media use, envy, and lower mental well-being. A second literature, on related concerns about advertising and psychological well-being, is beginning to emerge (Opree, Buijzen, & van Reijmersdal, 2016).…”
Section: "Of All the Characteristics Of Ordinary Human Nature Envy Imentioning
confidence: 98%
“…You may think you're not eating enough, but you're eating too much; or you might think you've walked enough, but really you haven't, and instead, you've lain on bed for 14 hours." One particular discrepancy between subjectivity and objectivity is that depression creates a tendency to view things more negatively [24]. As explained by Clinician 4…”
Section: Usefulness Of Behavioral Target Data In Counseling Objectivementioning
confidence: 99%